Supercooled dynamics of grain boundary particles in two-dimensional colloidal crystals. - Skinner, T; Aarts, D; Dullens, R (2011)
We experimentally investigate the dynamics of particles constituting grain boundaries in a two-dimensional colloidal crystal, using video-microscopy. A clear plateau in the mean square displacement of the grain boundary particles is found, followed by an upswing indicative of cage breaking. The van Hove correlation functions and the non-Gaussian parameter show that grain boundary particle dynamics are highly heterogeneous. Furthermore, we identified clusters of cooperatively moving particles and analyzed the time-dependence of the weight-averaged mean cluster size. We find good correlation between the behavior of the mean square displacement, and the time dependence of the non-Gaussian parameter and the cluster size, as also reported for various supercooled systems. Our results therefore provide experimental support for the similarity between particle dynamics in grain boundaries and in supercooled liquids as suggested by recent computer simulations.